Comparative Evaluation of the Accuracy of Electronic Apex Locator and Digital Radiography for Working Length Determination in Primary Teeth: A Systematic Review - Ishita Agrawal; Farhin Katge; Sanmati Pol; Devendra Patil; Vamsi Chimata; Debapriya Pradhan (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: It is challenging to perform a pulpectomy procedure in primary tooth because of its physiological root resorption and variation in root morphology. Working length measurement is considered to be one of the critical steps, as it determines the extent of obturation and apical seal.Purpose: To compare the accuracy of electronic apex locator (EAL) and digital radiography (DR) for working length determination in primary teeth.Materials and Method: In this systematic review, electronic databases and grey literature were searched from 1st January 2005 to 1st January 2023 for randomized control trial, non- randomized control trial, in vitro studies, ex vivo studies that compared accuracy of EAL and DR in primary teeth. Two reviewers independently identified studies, retrieved data, and assessed risk of bias using the revised and validated MINORS (methodological index for non-randomized studies) criteria.Results: Ten studies were included in qualitative analysis. Seven out of ten studies showed low risk of bias whereas other three studies showed high risk of bias. In view of methodological heterogeneity of the findings, a meta-analysis was not conducted.Conclusion: Available evidence suggests a moderate quality of evidence in this systematic review. Analyzing the ten studies included in this systematic review, the majority of studies showed statistically insignificant difference between EAL and DR. However, EAL was closer to actual WL as compared to DR. Based on the evidence that is currently available; EAL can be considered as an alternative for working length measurement in primary teeth.